2007
DOI: 10.1016/j.ydbio.2007.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Gcm2 is required for the differentiation and survival of parathyroid precursor cells in the parathyroid/thymus primordia

Abstract: The parathyroid glands develop with the thymus from bilateral common primordia that develop from the 3rd pharyngeal pouch endoderm in mouse embryos at about E11, each of which separates into one parathyroid gland and one thymus lobe by E13.5. Gcm2, a mouse ortholog of the Drosophila Glial Cells Missing gene, is expressed in the parathyroid-specific domains in the 3rd pouches from E9.5. The null mutation of Gcm2 causes aparathyroidism in the fetal and adult mouse and has been proposed to be a master regulator f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
131
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(140 citation statements)
references
References 73 publications
8
131
1
Order By: Relevance
“…Deficiency of Gcm2 in mice leads to the absence of parathyroid glands without affecting thymus formation (Liu et al, 2007). Notch-target Gata3 (Fang et al, 2007;Naito et al, 2011) is one of the upstream regulators of Gcm2, as Gata3 -/-mice showed no Gcm2 expression and no gland formation (Grigorieva et al, 2010).…”
Section: Parathyroid Rudimentmentioning
confidence: 99%
See 1 more Smart Citation
“…Deficiency of Gcm2 in mice leads to the absence of parathyroid glands without affecting thymus formation (Liu et al, 2007). Notch-target Gata3 (Fang et al, 2007;Naito et al, 2011) is one of the upstream regulators of Gcm2, as Gata3 -/-mice showed no Gcm2 expression and no gland formation (Grigorieva et al, 2010).…”
Section: Parathyroid Rudimentmentioning
confidence: 99%
“…homozygous null mutant mice, the expression of Pth is not initiated and no parathyroid glands are formed (Günther et al, 2000;Liu et al, 2007).…”
mentioning
confidence: 99%
“…By E11.5, the thymus-and parathyroid-fated domains can be recognized by Foxn1 and Gcm2 expression respectively. However, although these transcription factors regulate differentiation, they do not specify thymus versus parathyroid fate (Bleul et al, 2006;Liu et al, 2007;Nowell et al, 2011). A Hox-Pax-Eya-Six cascade is implicated upstream of thymus specification, but has not been directly linked to the establishment of thymus fate (Manley and Condie, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The first-identified drosophila GCM was identified as a gene responsible for a phenotype called glial cells missing, which is the gene name GCM derived (19,23). GCMa and GCMb are predominantly expressed in developing placenta and the parathyroid gland, respectively (5,16,29). GCMa instructs trophoblast stem cells to differentiate into syncytiotrophoblast cells (1,2).…”
Section: Introductionmentioning
confidence: 99%